POTENSI EKSTRAK BIJI ALPUKAT SEBAGAI KOMPONEN AKTIF PENGAWET DALAM EDIBLE FILM BERBASIS PATI UBI KAYU - Inayah, Istiyati; Nurminabari, Ina Siti; Ira Endah Rohima; Zahrah (Pasundan Food Technology Journal (PFTJ), 2025)
Edible films derived from natural materials have emerged as sustainable alternatives to conventional food packaging; however, their limited functional properties necessitate the incorporation of bioactive compounds. Avocado seed extract is a potential source of natural antibacterial agents, yet its application in edible film matrices remains underexplored. This study aimed to develop cassava starch–based edible films enriched with avocado seed extract and to evaluate their physicochemical characteristics and antibacterial properties. The ethanol extract of avocado seeds was characterized using GC–MS, analyzed for total polyphenol content, and assessed for antibacterial activity. Edible films were prepared from cassava starch, glycerol, and avocado seed extract at various concentrations (0–10% w/w). The films were evaluated for moisture content, water vapor transmission rate, solubility, water absorption, texture profile, and antibacterial activity. The results showed that the extract contained four dominant compounds—n-hexadecanoic acid, 2-(2-hydroxycyclooctyl)-furan, 5,10-pentadecadien-1-ol (Z,Z), and 1H-1,2,3-triazole-4-carboxaldehyde—with a total polyphenol content of 29.82%. At 10% extract concentration, the inhibition zone against Escherichia coli reached 15.44 mm. Incorporation of the extract significantly affected the films’ moisture content, solubility, water absorption, and antibacterial activity, but had no significant effect on water vapor transmission. The 5% extract formulation provided the best balance of mechanical strength, barrier properties, and antibacterial effectiveness. Overall, the addition of avocado seed extract demonstrates strong potential as a natural active packaging component to enhance food safety and extend shelf life.